ORAL MELANOMA: WHAT DOES THE DENTIST NEED TO KNOW? - Gabriel Bassan Marinho Maciel; Taline Laura Guse (Portal de Periódicos da Marinha do Brasil, 2024)
Oral melanoma is a malignant neoplasm of melanocytes, characterized by aggressive behavior and an extremely poor prognosis. Melanomas in the oral cavity are rare and are usually diagnosed at an advanced stage, reducing patient survival. The aim of this narrative literature review is to compile the essential aspects of oral melanoma and other pigmentations to guide early diagnosis by the dentist. Comprehensive searches were conducted in the PubMed, Embase, Lilacs, and Cochrane databases. Oral melanoma typically presents as a macule or nodule, brown or black in color, and may show variations in color and even depigmentation. It has a predilection for the palate and maxillary gingiva, is usually asymptomatic, and affects slightly more males, especially between the 4th and 7th decades of life. Although they share similar clinical characteristics with cutaneous melanoma, they are considered distinct variants. Dentists must be aware of the main clinical characteristics of oral melanoma and other pigmentations of the oral cavity to make an early diagnosis of the neoplasm and manage the case appropriately.